"THE NAVY THAT ALTEREDCOURSE" - Little, Ivor C. (Scientia Militaria - South African Journal of Military Studies, 2012)
The Republic of South Africa is continually in the news for one reason or another and most members of the world's naval fraternity have a very good idea of where it is even if their judgement as to what sort of a place it is may differ. Very few of them however have a clear picture of what sort of a navy it has and why. The South African Navy is in fact a most unusual one, having in recent years literally turned its back on its former blue water navy image and voluntarily scaled itself down to a coastel defence role - quite the opposite to what most navies aspire to and a dramatic change of attitude with far-reaching effects on naval strategy for the West. In case there are those who doubt that this last statement is in fact so, let us consider a few background facts.